Effect of pre artificial insemination administration of amoxicillin + cloxacillin on conception rate in normal and repeat breeding cross bred cattle - MAHTO, DINESH; SINGH, M P; SINGH, BALRAJ; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
A total number 6f 33 animals grouped under normal and repeat breeding category were treated with single dose amoxicillin+cloxacillin combinations. The amoxicillin + cloxacillin was infused intra-uterine 8-12 hrs pre insemination during estrous to evaluate the efficacy on the conception rate in normal and repeat breeder cows. In. normal animals the conception rate with pre A.I. treatment was 63.63 % as compared to 33.33 % for control group. Similarly in repeat breeding cows, the conception rate was 60.00 with pre A.I. treatment as compared to 16.66 % in control group. The differences were recorded to be non-significant.